Examining The Controversy Behind The Events Of the 30 September 1965 Movement - Yogi Pratama (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This research aims to describe the controversy behind the events of the 30 September 1965 movement. Starting from the controversy regarding the naming of the event, the mastermind and motive, genocide after the 30 September movement, the pretext for mass murder, to books and films that explain the events of the 30 September movement in 1965. Research methods uses historical or historical methods in the form of descriptive narrative through 4 stages of heuristics, source criticism, interpretation, and historiography. Based on research results, after the incident occurred, many controversies occurred, such as the naming of the event, there were various versions of G30S/PKI, which meant that the PKI was the mastermind, on the other hand, G30S, that the PKI was not one hundred percent the perpetrator, Gestapu meant the 30th September movement, and gestok meant the movement. one october. Then the masterminds of the incident were 5 versions of the PKI itself with the motive of wanting to change communist ideology, Suharto who wanted to get rid of Sukarno, Soekarno with the motive of getting rid of generals who were not pro him, the TNI AD because of dissatisfaction between the general staff and military leaders who were wallowing in wealth, and the CIA with the aim of preventing communism in Indonesia. The post-event genocide which caused controversy due to indiscriminate arrests and clear laws led to books and films appearing with different points of view regarding the 30 September movement in 1965. This research provides insight into the controversy behind the events of the 30 September movement in 1965 in Indonesia.